Effects of a career course on students’ career decision-making self-efficacy, indecision and difficulties - Lam, Michele Chee-Kuan (2016)
Many college students have difficulties deciding on a major or field of study at university. Hartman, Fuqua and Hartman (1983) reported that if undecided students did not receive help, they were more likely to drop out of school and to be unhappy with their eventual choice of career. Furthermore, undecided students may make poor career and academic choices which will impact their future (Gati, Krauz & Osipow, 1996; Fouad, Cotter & Kantamneni, 2009). While the need for career interventions has increased (Fouad et al., 2009; Reese & Miller, 2010), few studies have systematically evaluated the impact and outcomes of career interventions designed to reduce career indecision. In addition, the majority of studies were conducted on Western populations thereby restricting the generalisability of findings across cultures. Therefore, there is a need to investigate whether theory-based interventions that have shown positive outcomes on Western samples can be applied in a Southeast Asian context. This study aims to address this gap in research literature through examining the effects of an intervention to help Malaysian students increase their career decision-making self-efficacy, and reduce career indecision and career decision-making difficulties. This thesis describes the research work aimed at evaluating the effectiveness of a career course designed to help students make career decisions in a Southeast Asian context. It details the quasi-experimental longitudinal intervention utilising intervention and comparison groups that was carried out with first-year Malaysian college students. Participants in both groups were given questionnaires assessing career decision-making self-efficacy, career indecision and career decision-making difficulties at various time points. Results indicated that participants in the intervention group upon completion of the course experienced increased career decision-making self-efficacy and reduced career indecision. Participants in the intervention group also showed an overall decrease in career decision-making difficulties but further investigation revealed that the decrease was non-significant in one subcategory of difficulties, namely difficulties related to the lack of motivation. The implications of these findings are discussed in terms of existing literature and suggestions for further research are also included.